2005
DOI: 10.1593/neo.04448
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Epigenetic Changes of Components Affecting the WNT Pathway in Colorectal Carcinomas Stratified by Microsatellite Instability

Abstract: An unselected series of 310 colorectal carcinomas, stratified according to microsatellite instability (MSI) and DNA ploidy, was examined for mutations and/or promoter hypermethylation of five components of the WNT signaling cascade [APC, CTNNB1 (encoding beta-catenin), AXIN2, TCF4, and WISP3] and three genes indirectly affecting this pathway [CDH1 (encoding E-cadherin), PTEN, and TP53]. APC and TP53 mutations were each present more often in microsatellite-stable (MSS) tumors than in those with MSI (P < .001 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
74
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 42 publications
4
74
0
1
Order By: Relevance
“…In the case of APC similar results have been reported by Thorstensen et al [35], whereas in the case of K-RAS Konishi et al [36] and Jass et al [37] have shown that it is more frequently mutated in MSI-L than in MSS tumours. The CTNNB1 gene was only found to be mutated in 2 out of 50 tumours, which is in agreement with previously published data reporting that CTNNB1 mutations were present in up to 3% of the sporadic CRC analyzed [13][14][15][16] and that they are mainly associated with HNPCC [17].…”
Section: Discussionsupporting
confidence: 77%
“…In the case of APC similar results have been reported by Thorstensen et al [35], whereas in the case of K-RAS Konishi et al [36] and Jass et al [37] have shown that it is more frequently mutated in MSI-L than in MSS tumours. The CTNNB1 gene was only found to be mutated in 2 out of 50 tumours, which is in agreement with previously published data reporting that CTNNB1 mutations were present in up to 3% of the sporadic CRC analyzed [13][14][15][16] and that they are mainly associated with HNPCC [17].…”
Section: Discussionsupporting
confidence: 77%
“…Although in these CRCs no APC-MCR mutations or CTNNB1 exon 4 to 10 hotspot mutations were identified, alternative mechanisms may be operational to activate the WNT pathway, eg, methylation of the APC promotor regions and MSIrelated frameshift mutations in WNT pathway regulators, such as AXIN2. 53 In these patients with HPS, a median of only one adenoma (range, zero to five) was identified, suggesting that the WNT pathway may, indeed, be involved at some stage of carcinogenesis via the serrated pathway. Considering that no BRAF mutations or directly adjacent serrated polyps were found, it seems unlikely that these CRCs are the outcome of a proposed fusion pathway, but formally this cannot be excluded.…”
Section: Discussionmentioning
confidence: 92%
“…This stop codon results in Axin2 transcripts without the DIX domain (761-843 aa), needed for b-catenin binding of Axin2. 30 However, the demonstration of a novel heterozygous in-frame deletion of AXIN2 exon 7 in a MSI2 cancer (2%, Conversion of glycine to an aspartic acid at codon 90 (G90D) in the second HEAT repeat of PPP2R1B has been reported previously in lung and colon cancer. 21 These authors suggested that this codon might represent a hot spot for mutation in cancers.…”
Section: Discussionmentioning
confidence: 94%